Development Of Smart Navigation System For The Visually Impaired - Badruddin, Ahmad Aslam Ahmad (Universiti Sains Malaysia, 2017)
Smart navigation system for the visually impaired is very important for them to travel from one place to another. Compared to readily available devices such as white cane, guide dog and others, which are time consuming, expensive and potential injuries for the visually impaired, this project serves way better in reducing error potential. Ultrasonic sensors will be attached to the front, right side and to the left side. The front ultrasonic sensor is to detect any obstacle so that visually impaired can avoid it. The side sensors act as anti-veering to ensure the visually impaired stay on the track. GPS module with GSM module also used in this project, which is to trace the location of the visually impaired. With this, the visually impaired can go anywhere since their location can be traced by the guardian. Investigation on the ultrasonic sensors during walking is carried out. The performance of the GPS with GSM also analyzed. As a result, this system can be used as a navigation system to increase the performance in walking of the visually impaired to ensure they walk safely by understanding the surrounding environment.